Politicised Bureaucrats: Conflicting Loyalties, Professionalism and the Law in the Making of Public Services. Issue 3 (September 2022) - Andreetta, Sophie; Kolloch, Annalena
Abstract: Over recent years, public servants from across the world, from French nurses and Belgian social workers to Beninese judges, have been protesting their governments. These protests, some even overt, have erupted in response to specific policies imposed on them or needing to be enforced by them. This Special Issue, however, delves into diverse processes, strategies, actions and practices adopted by civil servants in delivering or administering a public service, be that health care, education, welfare and the like, by extension, seeking to redefine the state or the experience of the state (as a body of institutions, services, public policies, etc.) at the micro-level. Often daily practices of public servants when administering public services directly or indirectly challenge and undermine such legal and policy directives of the government that defy their own idea(l)s of stateness. These findings are drawn from recent works on the making of stateness, which explore the day-to-day work of public servants, especially their interaction with users and their exercise of discretion in implementing public policies. The studies focus on how public servants critically engage with the state and interrogate its policies, mainly to instil (or prevent) political change. A critical engagement with the conflicting loyalties of individual bureaucrats will expand our current understanding of street-level bureaucracies. That also entails observing and analysing their ambivalent responses to new governmental injunctions on a day-to-day basis and their attempts to reinterpret and redefine professionalism as they navigate their conflicting loyalties.